Individual Factors Associated with Women's Use of Mental Health Services during Incarceration: Targeting Programmatic Resources. Issue 3 (27th May 2021) - Casey, Rachel C.; Bentley, Kia J.
ABSTRACT: This study analyzed data from the Bureau of Justice Statistics Survey of Inmates in State Correctional Facilities to identify factors associated with the use of mental health services among incarcerated women (N = 2571). One quarter of the sample (25.3%) reported accessing mental health counseling during their incarceration, while 30.8% reported using psychotropic medications. Survivors of childhood sexual victimization were more likely to use psychotropic medication (OR = 1.45, p = .016) compared to women who had not experienced this form of violence. Women convicted of violent offenses were more likely to use both psychotropic medication (OR = 2.13, p < .001) and counseling services (OR = 1.57, p = .002). Correctional practitioners should considertargeting resources to address women's experiences as both victims and perpetrators of violence.